Determination of dimethylethylamine in air samples from iron foundries by isotachophoresis. - Hansen, L.; Sollenberg, Jan; Uggla, C. (Scandinavian Journal of Work, Environment & Health, 1985)
A method for the determination of dimethylethylamine in workroom air has been developed. Static gas standards of the amine in air were used to evaluate different sampling techniques. The analysis was performed by isotachophoresis. The sampling equipment of choice was midget impinger flasks of glass or polystyrene containing 10 ml of hydrochloric acid (50 mmol/l). The method was used in a field study of three different iron foundries where air samples were taken. The dimethylethylamine concentration found was in the range 0.5-155 mg/m3. No pretreatment of the samples was necessary, and no interfering substances from the air in the foundries affected the analysis.